The chick embryo chorioallantoic membrane (CAM). A multifaceted experimental model - Ribatti, Domenico (Mechanisms of development, 2016)
During avian development the mesodermal layers of the allantois and chorion fuse to form the chorioallantoic membrane (CAM). This structure rapidly expands generating a rich vascular network that provides an interface for gas and waste exchange. The CAM allows to study tissue grafts, tumor growth and metastasis, wound healing, drugs delivery and toxicologic analysis, and angiogenic and anti-angiogenic molecules. The CAM is relatively simple, quick, and low-cost model that allows screening of a large number of pharmacological samples in a short time; does not require administrative procedures for obtaining ethics committee approval for animal experimentation. Moreover, being naturally immunodeficient, the chick embryo may receive transplantations from different tissues and species, without immune responses. •The CAM is relatively simple, quick, and low-cost model.•It allows screening of a large number of pharmacological samples.•The main limitation of CAM is a nonspecific inflammatory reaction.